Justification of the cognition subject problem in the methodology of contemporary human - Mubariz H. Mustafayev, Bakhsheyish M. Asgarov, (Opción, 2019)
The research is devoted to the study of the essential characteristics of the cognition subject. As an illustrative material, the experience of post-Soviet countries with dogmatic ideology and destructive methodology was used. It is found that only a liberal-minded subject and a methodology developed on the supremacy of spiritual values are able to perfect a reverential approach to the person and the world as a whole. In conclusion, it was established that in the cognitive process the key role is played by the subject of cognition. But his essential characteristics directly depend on the historical era.